Altered intrinsic regional brain spontaneous activity in patients with comitant strabismus: a resting-state functional MRI study - Huang X (Dove Medical Press, 2016)
Xin Huang,1,2,* Sheng-Hong Li,3,* Fu-Qing Zhou,3 Ying Zhang,1 Yu-Lin Zhong,1 Feng-Qin Cai,3 Yi Shao,1 Xian-Jun Zeng3 1Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Clinical Ophthalmology Institute and Oculopathy Research Centre, Nanchang, 2Department of Ophthalmology, The First People’s Hospital of Jiujiang City, Jiujiang, 3Department of Radiology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Medical Imaging Research Institute, Nanchang, Jiangxi, People’s Republic of China *These authors contributed equally to this work Objective: To investigate the underlying regional homogeneity (ReHo) of brain-activity abnormalities in patients with comitant strabismus (CS) and their relationship with behavioral performance.Methods: Twenty patients with CS (ten men and ten women) and 20 (ten men and ten women) age-, sex-, and education-matched healthy controls (HCs) underwent resting-state functional magnetic resonance imaging scans. The ReHo method was used to assess local features of spontaneous brain activities. Patients with CS were distinguished from HCs by receiver operating characteristic curve. Correlation analysis was performed to explore the relationship between the observed mean ReHo values of the different brain areas and behavioral performance.Results: Compared to HCs, the patients with CS showed significantly increased ReHo values in the right inferior temporal cortex/fusiform gyrus/cerebellum anterior lobe, right lingual gyrus, and bilateral cingulate gyrus. We did not find any relationship between the observed mean ReHo values of the different brain areas and behavioral performance.Conclusion: CS causes dysfunction in many brain regions, which may explain the fusion compensation in CS. Keywords: comitant strabismus, regional homogeneity, functional magnetic resonance imaging, resting state